Rice Husk Ash as a Renewable Source for the Production of Value Added Silica Gel and its Application: An Overview - Ram Prasad; Monika Pandey (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
In recent years, silica gels have developed a lot of interest due to their extraordinary properties and their existing and potential applications in science and technology. Silica gel has a wide range of applications such as a desiccant, as a preservation tool to control humidity, as an adsorbent, as a catalyst and as a cata-lyst support. Silica gel is a rigid three-dimensional network of colloidal silica, and is classified as: aqua-gel, alco-gel, xero-gel and aero-gel. Out of all known solid porous materials, aero-gels are particularly known for their high specific surface area, high porosity, low bulk density, high thermal insulation value, ultra low dielectric constant and low index of refraction. Because of these extraordinary properties silica aero-gel has many commercial applications such as thermal window insulation, acoustic barriers, super-capacitors and catalytic supports. However, monolithic silica aero-gel has been used extensively in high energy physics in Cherenkov radiation detectors and in shock wave studies at high pressures, inertial confinement fusion (ICF) radio-luminescent and micrometeorites. Silica gel can be prepared by using various sol gel precursors but the rice husk (RH) is considered as the cheapest source for silica gel production. Rice husk is a waste product abundantly available in rice producing countries during milling of rice. This review article aims at summarizing the developments carried out so far in synthesis, properties, characterization and method of determination of silica, silica gel, silica aero-gel and silica xero-gel. The effect of synthesis parameters such as pH, temperature of burning the rice husk, acid leaching prior to formation of rice husk ash (RHA) on the properties of final product are also described. The attention is also paid on the application of RH, RHA, sil-ica, silica aero-gel and silica xero-gel. Development of economically viable processes for getting rice husk silica with specific properties assumes importance at this juncture. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)